Endemic species of Impatiens spp. (Balsaminaceae) in Sumatra and its possibility as an ornamental plants - NANDA UTAMI (Society for Indonesian Biodiversity, 2006)
Inventory study of Impatiens has been done in Sumatra. Twenty five species of Impatiens were colleted from several research sites. Based on the morphological flower and their color, 9 species among them, such as I. tujuhensis Utami & T. Shimizu, I. elephanticeps Grey-Wilson, I. sorikensis N. Utami, I. pilosivitata Grey-Wilson, I. steenisii Grey-Wilson, I. sidikalangensis Grey-Wilson, I. pseudoperezii Grey-Wilson, I. rubriflora Grey-Wilson, and I. batanggadisensis N. Utami have potential as ornamental plants. I. tujuhensis Utami et T. Shimizu is closely related to I. elephanticeps Grey-Wilson. The two taxa are characterized by lower sepal like an elephantâ€™s trunk, but I. tujuhensis differs from I. elephanticeps in having leaf lamina pubescent above with crenulated margins, petioles with several stipulated glands, the smaller tepals densely pubescent outside, but with lateral united petals which are bent backward along the midrib, the upper portions of the lateral united petals with a brown-purple patch and the dorsal petal with dense brown-purple reticulation inside. I. sorikensis N. Utami finds its closest ally in I. pilosivitata Grey-Wilson. They differ in a number of important aspects: the shape of the lateral petals, the color of the flowers, and the shape of the leaves. I. steenisii Grey-Wilson has a broader navicular lower sepal with a short incurved spur; flowers when viewed from the front have a curious bilateral asymmetry caused by a twist in the lateral united petals. I. sidikalangensis Grey-Wilson is characterized by rather flat or shallowly cupped, white or pale pink flowers, the dorsal petal and the base of the two lateral petals stained with reddish or lilac-purple. I. pseudoperezii Grey-Wilson has large pink or purple, with long curved spurs. I. rubriflora Grey-Wilson is the only species with red flowers, with its stout inflorescence and narrow bucciniform lower sepal. I. batanggadisensis N. Utami is characterized by yellow flowers with red markings on the bases of the two lateral petals, emarginated lower petals, and glabrous leaves. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Impatiens, Balsaminaceae, wild plant, endemic, ornamental plants